Training need analysis of foreign workers to enhance productivity / Nor Zairaa Muhamad - Muhamad, Nor Zairaa (Faculty of Plantation and Agrotechnology, 2017)
Training need analysis is the method of determining if training need exist and if not, what training is required to fill the gap and the factor that contribute to training implement. The purpose of this research study is determine relationship of each factor towards need of training and also to identify the most influence factor that affects the training need in estate. A survey of 108 workers was carried out in Espek Ladang Risda Serigala,Perak.